Characterize ZnO Nanoparticles’ Morphology and Crystal Structure, Respectively To Giving This Material for Further Learning To Students - Elza Rachman Panca Priyanda; Futri handayani; Oktri Lestari; Riri Amanda Fitriana; Lila wahyuni (Ridwan Institute, 2021)
This study aims to characterize Zno Nanoparticles’ Morphology and Crystal Structure, Respectively to Giving This Material for Further Learning to Students. The method used in this study: (i) understanding how to synthesize ZnO nanoparticles using a liquid-phase synthesis (ii) implementation of ZnO nanoparticles to students and analysis their comprehension using Transcript Based Lesson Analysis (TBLA) on the Learning Video Recording and Adaptation Learning Transcript. To support this study, several analyses were done, such as a scanning electron microscope (SEM) and X-ray diffraction (XRD) to characterize ZnO nanoparticles’ morphology and crystal structure, respectively, prior to giving this material for further learning to students. Experimental results showed that the use of ZnO is effective to improve the student comprehension. Students become more serious in listening during the learning process. They also have been more curious to study science and technology.